Prevalence and risk factors of restless legs syndrome in patients of migraine without aura - Nagaraj, Karthik; Patil, Ramesh (International Journal of Advances in Medicine, 2019)
Background: An association between migraine and Restless Legs Syndrome (RLS) has been proposed due to shared dopaminergic dysfunction. Both have substantial effects on the quality of life. Identifying co morbidities of migraine helps in optimizing patient management. Objectives To study the prevalence of RLS in patients of migraine without aura, and associated co morbidities of RLS. Methods: This was a hospital based prospective observational study. All patients diagnosed as Migraine without aura as per ICHD-3 criteria completed the questions regarding migraine headache, Migraine Disability Assessment (MIDAS) questionnaire, Hospital Anxiety and Depression Scale (HADS), Pittsburgh Sleep Quality Index (PSQI) and International RLS Study Group (IRLSSG) Rating Scale. RLS was diagnosed using the IRLSSG criteria. Serological investigations were done to look for secondary causes of RLS. Results: Out of 200 consecutive patients of migraine without aura were included in the study over a period of 18 months. Frequency of RLS was 13.5% (n=27). All patients had primary RLS. Mean PSQI score was higher in the patients of migraine without aura with RLS than in non RLS patients of migraine without aura (3.30±2.66 vs 2.24±2.03 p≤0.0168). Poor sleep quality, anxiety, depression was found in 9%, 8% and 2.5% respectively in patients of migraine without aura. Conclusions: An association between migraine without aura and RLS was demonstrated. Migraine without aura was associated with increased frequency of poor sleep quality, anxiety and depression.